MAC protocol for low-power real-time wireless sensing and actuation - Afonso, José A. (2006)
This paper presents LPRT, a new medium access control (MAC) protocol for wireless sensing and actuation systems. Some of the characteristics of the proposed protocol are low power consumption, support for real-time and loss intolerant traffic through contention-free operation and a retransmission scheme, flexibility, and high throughput efficiency. The LPRT protocol was implemented it in the MICAz motes, a platform for the development of wireless sensor networks. We also briefly describe a wireless hydrotherapy application that benefits from the use of the proposed protocol. This paper also provides experimental results and comparison of the proposed protocol with the CSMA/CA protocol of IEEE 802.15.4.